Fuzzy logic-based smart parking system - Tuncer, Taner; Yar, Okan (International Information and Engineering Technology Association, 2019)
Wireless sensor networks consist of many sensors designed to provide an information flow from a specific area. Sensors communicate with each other to receive information from the physical environment they are in and transfer the results to the electronic environment. In recent years, advances in wireless sensor networks have made it necessary to control and monitor large physical fields, and collect and store the resulting data. In particular, it is very important to collect and process data on infrastructure, air pollution, traffic and many other similar issues in crowded cities. The smart city structure aims to combine data originating from different sources for different purposes. This study proposes a fuzzy logic-based solution to the driver parking problem. This solution recommends the best parking spot to the customer by processing the number of empty parking spaces in different places within the city, the distance from the customer to the parking spot and the relevant traffic information. The customer can find the best parking spot using the developed android-based interface. First, the number of empty spaces and the locations of the parking areas were stored in a cloud database. The time associated with the traffic information and the routes between the customer and the car parking spots were obtained using Google services. While the inputs for the developed fuzzy logic-based system were the number of empty parking spaces, and the distance and time, the output is the recommendation or the car park preferred by the customer. Thus, a smart solution to the parking problem is presented and the availability of parking spaces, prevention of lost customer time and the reduction of costs has all been achieved. © 2019 International Information and Engineering Technology Association. All rights reserved.
Keywords: Fuzzy logic; Mobile communication; Wireless sensor networks